Comparative Evaluation of Dental Implant Failure among Healthy and Well-Controlled Diabetic Patients—A 3-Year Retrospective Study - Sghaireen, Mohammed Ghazi; Alduraywish, Abdulrahman A.; Srivastava, Kumar Chandan; Shrivastava, Deepti; Patil, Santosh R; Al Habib, Selham; Hamza, May; Ab Rahman, Saifulizan; Lynch, Edward; Alam, Mohammad Khursheed (International journal of environmental research and public health, 2020)
Diabetes mellitus is known to compromise the various aspects of homeostasis, including the immune response and the composition of oral microflora. One of the oral manifestations of diabetes mellitus is tooth loss and the survival rate of dental implants chosen as a treatment modality for its rehabilitation is controversial. The current study aims to evaluate and compare the failure rate of dental implants between well-controlled diabetic and healthy patients. A retrospective study of case-control design was conceptualized with 121 well-controlled diabetic and 136 healthy individuals. Records of subjects who had undergone oral rehabilitation with dental implants between the periods of January 2013 to January 2016 were retrieved. Post-operative evaluation was carried out for all patients for about three years to assess the immediate and long-term success of the procedure. From a total of 742 dental implants, 377 were placed in well-controlled diabetic patients (case group) and 365 in healthy subjects (control group). A comparable (9.81%), but non-significant (p = 0.422) failure rate was found in the case group in comparison to the control group (9.04%). A non-significant (p = 0.392) raised number (4.98%) of failure cases were reported among females in comparison to males (4.44%). In respect to arch, the mandibular posterior region was reported as the highest failure cases (3.09%; p = 0.411), with 2.29% of cases reported in the mandibular anterior (p = 0.430) and maxillary posterior (p = 0.983) each. The maxillary anterior region was found to have the least number (1.75%; p = 0.999) of failure cases. More (4.98%; p = 0.361) cases were reported to fail during the functional loading stage in contrast to osseointegration (4.44%; p = 0.365). A well-controlled diabetic status does not impose any additional risk for individuals undergoing dental implant therapy.